Iron oxide nanoparticles enhancing magnetic resonance imaging: A review of the latest advancements - Samia Faisal O. Aboushoushah (Journal of Science: Advanced Materials and Devices)
This review explores the advancements in iron oxide nanoparticles (IONPs) as MRI contrast agents, emphasizing their synthesis, surface engineering, and impact on MRI contrast enhancement. While gadolinium-based contrast agents (GBCAs) remain the clinical standard for T1-weighted imaging, their safety concerns have driven research toward IONPs as promising alternatives. Ultra-small IONPs (<5 nm) exhibit strong T1 contrast enhancement, while larger IONPs (>20 nm) provide superior T2 contrast due to their high r2 relaxivity. Additionally, recent developments in T1/T2 switchable IONPs enable dynamic contrast modulation through controlled size, shape, and stimuli-responsive surface modifications, enhancing tumour imaging specificity. This review examines diverse surface engineering strategies, including protein, polysaccharide, polymer, lipid, mesoporous silica, and hybrid coatings, that enhance biocompatibility, circulation time, and targeting efficiency. Despite their potential, IONPs face challenges in clinical translation, including regulatory hurdles, inconsistent targeting efficiency, and long-term safety concerns. Addressing these limitations through optimized formulations, biocompatibility-focused designs, and rigorous preclinical evaluation will be crucial for their successful integration into clinical MRI diagnostics. Our findings suggest that IONPs not only mitigate many limitations of conventional contrast agents but also pave the way for precision imaging and personalized medicine, redefining the future of MRI contrast technology.